KONSELING BAGI ANAK BERBAKAT AKADEMIK - Rochmat Wahab (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Counseling for the Academically Gifted Children. The number of academically gifted children is quite high distributed in all areas. The academically gifted children will be benefecial for themselves and other people, if they can develop optimally. There are many academically gifted children who are succesful in their life; however we can find some who are in difficulty. They need counseling services. There are some important issues in counseling, especially for the academically gifted children, such as: (1) divergent thinker, (2) excitability, (3) sensitivity, (4) perceptiveness, (5) entelechy. (6) self-concept, (7) counseling with parents, and (8) underachievement. To help them face important issues, social-personal counseling, academic counseling, and career counseling are necessary. These three counseling approaches can be conducted simultaneously, depending on their needs. The models and strategies of counseling for the academically gifted children are therapeutic, preventive, and developmental models. The choice of models is strongely determined by the need of effective counseling, in order to achieve the optimal result. To establish the effective counseling, it is necessary that counseling services should be conducted by professional counselors. Keywords: counseling, academically gifted children